2021
DOI: 10.5851/kosfa.2020.e99
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics and Anti-Diabetic Effect of Pediococcus pentosaceus KI62

Abstract: The purpose of this study is to examine the physiological characteristics and anti-diabetic effects of Pediococcus pentosaceus KI62. The α-amylase and α-glucosidase inhibitory activity of P. pentosaceus KI62 was 94.86±3.30% and 98.59±0.52%, respectively. In MRS broth containing 3% maltodextrin inoculated by P. pentosaceus KI62, the amounts of short chain fatty acids (SCFA) were propionic acid 18.05±1.85 mg/kg, acetic acid 1.12±0.07 g/100 mL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In addition, prior studies have shown that various strains of P. pentosaceus have anti-inflammatory, anticancer, antioxidant, detoxification, and lipid-lowering effects (Chung et al 2021;Jiang et al 2021;Li et al 2021;Dong et al 2022). Notably, in line with our findings, there were indications of encouraging adherence to P. pentosaceus (Kim et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, prior studies have shown that various strains of P. pentosaceus have anti-inflammatory, anticancer, antioxidant, detoxification, and lipid-lowering effects (Chung et al 2021;Jiang et al 2021;Li et al 2021;Dong et al 2022). Notably, in line with our findings, there were indications of encouraging adherence to P. pentosaceus (Kim et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The authors suggest that this can be an interesting property. It could be used as an anti-diabetic probiotic [62].…”
Section: Qualitative and Quantitative Hydrolases Analysismentioning
confidence: 99%
“…To measure the degree to which goat meat extract inhibits the digestion and absorption of monosaccharides, the α-glucosidase enzyme reaction of the extracts was evaluated according to the methods developed by Kim et al (2021) and Si et al (2010). Briefly, 50-μL aliquots of HE, HWE, and EE were mixed with 50 μL of α-glucosidase (Sigma-Aldrich, St. Louis, USA) in 50 μL of 200 mM potassium phosphate buffer (pH 6.5) (Sigma-Aldrich).…”
Section: α-Glucosidase Inhibitory Activitymentioning
confidence: 99%